2013
DOI: 10.1007/s10661-013-3455-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of poly-aromatic hydrocarbons (PAHs) in the aquatic species of Suez Gulf water along El-Sokhna area to the Suez refineries

Abstract: The Egyptian Red Sea environment especially along El-Sokhna area to the Suez refineries (Suez) is severely contaminated with organic compounds, as well as overfishing. This may be well contributory to recent serious declines in fish stocks. Fish embryos are also particularly vulnerable to oil exposure, even at extremely low concentrations of less than one part per billion. Consequently, even traces of oil pollution at levels often considered safe for wildlife can cause severe damage to fish. Sixteen polycyclic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…They mentioned that the petroleum refineries are the foremost continuous source of pollution by both heavy metals and organic contaminants in northwestern Suez Gulf region. Ali et al (2014) found concentrations of PAHs (399.616 up to 67631.779 ng/g) especially six rings members in fish samples collected along north Suez Gulf, that are high enough to cause lethal toxicity effect by accumulation. Farid et al (2014) determined petroleum pollutants in Suez Bay coastal waters with concentrations amounting to 3.88-37.69 mg/ml.…”
Section: Introductionmentioning
confidence: 94%
“…They mentioned that the petroleum refineries are the foremost continuous source of pollution by both heavy metals and organic contaminants in northwestern Suez Gulf region. Ali et al (2014) found concentrations of PAHs (399.616 up to 67631.779 ng/g) especially six rings members in fish samples collected along north Suez Gulf, that are high enough to cause lethal toxicity effect by accumulation. Farid et al (2014) determined petroleum pollutants in Suez Bay coastal waters with concentrations amounting to 3.88-37.69 mg/ml.…”
Section: Introductionmentioning
confidence: 94%
“…The PAHs is subject to microbial degradation which may be a rather rapid process in aerobic environments. However, if the PAHs are buried within the anaerobic sediments, bio-degradation proceeds very slowly [17].…”
Section: Introductionmentioning
confidence: 99%
“…The PAHs is subject to microbial degradation which may be a rather rapid process in aerobic environments. However, if the PAHs are buried within the anaerobic sediments, bio-degradation proceeds very slowly [17].…”
Section: Introductionmentioning
confidence: 99%